Elementary English teaching: a door to the American and native culture - Karol Cubero Vázquez (Ensayos Pedagógicos, 2009)
Last year a friend of mine was dating an American girl. During their passionate relationship, he tells his American girlfriend, «Til give you a ring tomorrow.» Trying to say that he would cali her by phone, but she understood that he had offered her a jewel. Unfortunately, the reíationship didn't survive due to this misunderstanding and my friend got a broken heart.